Leveraging Dynamic Capabilities For Strategic Alignment Of Csr Initiatives With SDGS: A Conceptual Framework - Brian Hamisi Kitsao; Ajai Prakash (Citakonsultindo, 2025)
Corporate Social Responsibility (CSR) has transitioned from merely being charity focused towards the incorporation of strategic practices that aid in impacting society in a more sustainable manner. United Nations set up SDGs in 2015 which have since then become a universal standard that organizations use to align with socio-economic objectives in general. For an efficient alignment of SDGs with CSR, a dynamic approach is needed to adapt to changes in the business environment. CSR keeps on changing with evolving social, environmental and market conditions. Since various factors define CSR in today’s world, it is imperative that organizations incorporate efficient strategies to have a long-lasting difference. This paper presents a conceptual framework that leverages dynamic capabilities to facilitate the strategic alignment of CSR initiatives with the SDGs. The focus is on how dynamic capabilities (DCs) can be applied when linking CSR and SDGs. This provides a good model that strategists and policy makers can leverage to improve the impact of CSR initiatives to enhance sustainability as envisaged in the SDGs. This way, businesses can attain their working goals and objectives and also contribute in positively impacting society to achieving the SDGs.